Lasten psykososiaalisen hyvinvoinnin ja psykologisen joustavuuden edistäminen mobiilipelin avulla - Lemmetyinen, Lari (2024)
Child and adolescent mental health problems are still a major ongoing issue in the society. Mental health care services only have limited resources for support, which has led to a high prevalence of young people outside seeking treatment. Digital mental health interventions provide a new and innovative approach to answer this treatment gap. The aim of this study was to examine whether a mobile game based on acceptance and commitment therapy could be used as an intervention to promote psychosocial well-being and psychological flexibility among 7–9-year-old schoolchildren (n=168). Intervention group played the game once a week with a total of four sessions during regular school hours. The results showed that psychological flexibility is associated with psychological well-being already among 1-3. grade children (r=.47). However, results also indicated that intervention was not detected significant between the intervention and control group. Further analysis was conducted based on the baseline level of psychosocial symptoms among participants. Children were divided into subgroups of high level (SDQ score 15+) and normal level of symptoms (SDQ score <15) based on their first measurement. Due to the small sample size of the subgroups, analysis was restricted to comparing within-group changes and effect sizes. After addressing the baseline level of symptoms, results showed a clear difference in the intervention group between children who reported high symptoms and whose symptoms were on a normal level. The subgroup that scored over the clinical cutoff point (n=17) had a major decrease in their symptoms (d=0,90), whereas children who reported normal level of symptoms (n=63) had basically no change in their symptoms. This study indicates that especially children who suffer from mental health related problems could benefit from similar games, even though the observed decrease in their symptoms could not be addressed as the effect of the intervention.